PENGARUH PENGETAHUAN PAJAK, KESADARAN WAJIB PAJAK, DAN PERSEPSI WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI YANG MENJALANKAN USAHA DAN PEKERJAAN BEBAS DI KANTOR PELAYANAN PAJAK PRATAMA SEMARANG BARAT - Meysari, 11.05.52.0058 (Students Journal of Accounting and Banking, 2013)
This study aims to examine and analyze the effect of knowledge about taxes, taxpayer awareness, perceptions about tax penalties, perceptions about service tax authorities and perceptions about the criteria of individual taxpayer compliance on individual the taxpayer compliance.The population in this study were individual taxpayers who carries on business and professional services that report SPT in the KPP Semarang Barat. Determination of individual taxpayers which will be choosen is used simple random sampling techniques. Where the individual taxpayers being randomly selected without regard to particular strata or levels.Based on the results of test performed can be seen that the knowledge about taxes, taxpayer awareness, perceptions about tax penalties, perceptions about service tax authorities and perceptions about the criteria of individual taxpayer compliance have positive and significant effect on individual taxpayer compliance.Keywords: knowledge about taxes, taxpayer awareness, perceptions about tax penalties, perceptions about service tax authorities and perceptions about the criteria of individual taxpayer compliance and individual taxpayer compliance.